Tinjauan Penerapan Kesehatan dan Keselamatan Kerja Proyek Jalan, Lereng dan Jembatan pada Masa New Normal Pandemi Covid-19 di Sulawesi Tengah - N. Nirmalawati; D.N. Nugroho (Civil Engineering Department, Tadulako University, 2023)
The implementation of Occupational Health and Safety in construction work needs to be considered so that accidents do not occur. Likewise, the survey project for roads, slopes and bridges during the new normal period of the Covid-19 pandemic needs to be reviewed, because there are deficiencies caused by various factors. Therefore, research was carried out to find out the factors that influence the implementation of Occupational Health and Safety during a pandemic and minimize the risk of accidents. This is a quantitative descriptive study, with a population of 94 respondents. Primary data is done by filling out a questionnaire and using photographs, while secondary data is the required project data. Data analysis uses descriptive statistics and Relative Rank Index. The results of the study of the five main factors that influence the implementation of OHS for road, slope and bridge survey projects are: (1) Human factors: work arrangements and the obligation to use PPE as well as strict supervision necessary to protect workers from the risk of accidents RRI value = 0.934; (2) Environmental factors: available first aid facilities RRI value = 0.930; (3) Equipment factor: working equipment used is always in good condition RRI value = 0.915; (4) Environmental factors: there is a room for resting and a kitchen along with drinking water for workers RRI value = 0.911; (5) Equipment factor: use of appropriate according to the type of work RRI value = 0.896. The results of photographic analysis in the field concluded that the implementation of Construction Health and Safety during the New Normal Period of the Central Sulawesi Covid-19 Pandemic was well implemented. But there are still some workers who still neglect personal safety when doing work by not using personal protective equipment on the grounds that they are not used to it.